Prospective Associations between Single Foods, Alzheimer’s Dementia and Memory Decline in the Elderly - Fischer K; Melo van Lent D; Wolfsgruber S; Weinhold L; Kleineidam L; Bickel H; Scherer M; Eisele M; van den Bussche H; Wiese B; König H-H; Weyerer S; et al. (MDPI (Basel, Switzerland), 2018)
Background: Evidence whether single “cognitive health” foods could prevent cognitive decline is limited. We investigated whether dietary intake of red wine, white wine, coffee, green tea, olive oil, fresh fish, fruits and vegetables, red meat and sausages, assessed by a single-food-questionnaire, would be associated with either incident Alzheimer’s dementia (AD) or verbal memory decline. Methods: Participants aged 75+ of the German Study on Aging, Cognition and Dementia in Primary Care Patients (AgeCoDe) cohort were regularly followed over 10 years (n = 2622; n = 418 incident AD cases). Multivariable-adjusted joint modeling of repeated-measures and survival analysis was used, taking gender and Apolipoprotein E4 (APOE ε4) genotype into account as possible effect modifiers. Results: Only higher red wine intake was associated with a lower incidence of AD (HR = 0.92; P = 0.045). Interestingly, this was true only for men (HR = 0.82; P < 0.001), while in women higher red wine intake was associated with a higher incidence of AD (HR = 1.15; P = 0.044), and higher white wine intake with a more pronounced memory decline over time (HR = −0.13; P = 0.052). Conclusion: We found no evidence for these single foods to be protective against cognitive decline, with the exception of red wine, which reduced the risk for AD only in men. Women could be more susceptible to detrimental effects of alcohol.
Keywords: Alzheimer´s dementia; apolipoprotein E ε4; cognitive decline; dementia; food intake; gender; memory decline; Age Factors; Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Cognitive Aging; Female; Food; Geriatric Assessment; Germany; Humans; Incidence; Male; Memory; Memory Disorders; Mental Status and Dementia Tests; Neuropsychological Tests; Prospective Studies; Protective Factors; Risk Factors; Sex Factors; Time Factors; Wine